المصلحة المرسلة (اعتبار حجيتها وارتباطها بكمال الشريعة الإسلامية): Al-Maslaḥah Al-Mursalah (its Authenticity and its Relation to the Perfection of Islamic Law) - Muhammad Taufan Djafri; Sayyid Tasdiq; Anugrah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research discusses the concept of al-Maslaḥah al-Mursalah and the jurists' views on its authenticity and limitations in its application. It also examines how the concept of al-Maslaḥah al-Mursalah serves as evidence of the perfection of Islamic law. The study aims to explore the concept of al-Maslaḥah al-Mursalah, its authenticity among jurists, its rules of application, and its connection to the completeness of Islamic law. The research is restricted to two main issues: first, the views of jurists on the authenticity of al-Maslaḥah al-Mursalah, and second, the rules governing its application and its relation to the perfection of Islamic law. The researcher adopts inductive, analytical, and historical approaches. The study concludes that jurists differ on the authenticity of al-Maslaḥah al-Mursalah, but in practice, they have applied it to various contemporary issues. Additionally, its application follows established rules by jurists, and it demonstrates the flexibility and validity of Islamic law in all times and places, reflecting the law's perfection.